If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 = 7x + 2(x + -3) Reorder the terms: -6 + 5x = 7x + 2(x + -3) Reorder the terms: -6 + 5x = 7x + 2(-3 + x) -6 + 5x = 7x + (-3 * 2 + x * 2) -6 + 5x = 7x + (-6 + 2x) Reorder the terms: -6 + 5x = -6 + 7x + 2x Combine like terms: 7x + 2x = 9x -6 + 5x = -6 + 9x Add '6' to each side of the equation. -6 + 6 + 5x = -6 + 6 + 9x Combine like terms: -6 + 6 = 0 0 + 5x = -6 + 6 + 9x 5x = -6 + 6 + 9x Combine like terms: -6 + 6 = 0 5x = 0 + 9x 5x = 9x Solving 5x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 5x + -9x = 9x + -9x Combine like terms: 5x + -9x = -4x -4x = 9x + -9x Combine like terms: 9x + -9x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 6x(2t-4)=48-6t | | 2y^2*3x=6xy^2 | | x*2+x=387 | | -31/2/2 | | -x^2+100x-1600=0 | | (2ab-2ac-2bc)(ab+ac+bc)= | | (x^2-5x+3)(2x^2+x-7)=0 | | (x-7)(x-4)=0 | | 8a^3+64b^3= | | 63/40= | | 0=3x^2+18x+18 | | 2/5m=8 | | -y+5.3+(7.2y-9)=6.2y+n | | 1188=-2x^2+98x | | x^2-63=18x | | x^2-23x=-132 | | 2(2t-4)=16+2t | | x^2-23x=-32 | | -4a+b=43 | | 4a+8b=20 | | 8x^3+81x^2-42x-8=-33.5 | | b=4/7=-3 | | 0.5(4x+8)=1.1-(x+2) | | 3/(8-7i)=0 | | 2x(10x+8)=-3(x+1) | | 1x^14=1.04 | | f(x)=x^4+3x^3-mx^2-nx-18 | | 2(5z-1)-3(z+6)=2(z+1) | | 2(5z-1)-3(z+6)=2(2+1) | | y=x^2-8lnx | | 3x-x+3=.71 | | 3x-x+3=.714 |